SOSIALISASI PADA MASYARAKAT KABUPATEN PANGANDARAN MENGENAI BAHAYA MEMBUANG SAMPAH DI SUNGAI - Supian, Sudradjat; Hiwari, Hazman; Subiyanto, Subiyanto (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Garbage is one of the problems that often occur in the community, especially in the disposal and handling of its existence. The Integrative KKNM-PPMD activity is a form of community service which based on Tridharma state of universities, can be used as a small deterrent to introduce and encourage clean action to the community to maintain the cleanliness of the environment. The purpose of this study is to educate the public about the dangers of dumping activities in the river. The activities carried out in 2 methods—first, socialization in the form of delivering information about the dangers of littering. Second, clean action activities participated in all communities around the Cikidang river. Implementation of this activity, it is expected the community can care about the cleanliness of the environment, including the river area.